La institucionalización de los sistemas de partidos en América del Sur (2000-2013) : una nueva mirada al concepto y su operacionalización - Nerea Ramírez García (2019)
In recent years, the experience of some Latin American countries has countered the classical theories about the institutionalization of party systems, generating a new wave of studies. This paper contributes to this debate by analyzing the institutionalization of party systems in South America during the period 20002013. The selected cases are Argentina, Bolivia, Brazil, Chile, Colombia, Ecuador and Uruguay. After a theoretical revision of the concept and its limitations, a new operationalization is proposed that aims to generate more precise measurements. By understanding institutionalization as electoral stability, the stability of partisan supply and interpartisan stability is operationalized through the exogenous volatility of the party system, the fluidity of the party system, and the structure of the competition of the party system. A Comparative Qualitative Analysis shows that South American systems can be institutionalized even though they do not have the stability dimension of the institutionalized partisan offer. Thus, from an aggregate index formed by the other two dimensions we conclude that the region is heterogeneous. Bolivia and Ecuador are incipient systems; Argentina and Colombia are fuzzy systems; Brazil and Uruguay are relatively institutionalized; and, Chile is fully institutionalized. Finally, after analyzing the impact of robust partisan organizations, programmatically structured parties and the positive economic context, the causal equifinality of institutionalization is confirmed. Specifically, two combinations of these conditions are sufficient: robust partisan organizations and a positive economic context or partisan organizations robust and programmatically structured. In addition, it is found that robust partisan organizations are a necessary condition for systems to be institutionalized, but programmatically structured parties are not.